Hubungan Frekuensi Antenatal Care Dengan Kejadian Anemia Pada Ibu Hamil Trimester III Di Rsud Nganjuk Tahun 2017 - Sumy Dwi Antono (coba, 2017)
Background: Antenatal Care is supervison before delivery especially knowing growth and development of fetus in uterus. The purpose of this study is to conceive the relationship between the frequency of ANC (Antenatal Care) with the incidence of anemia in the mother trimester III RSUD Nganjuk 2017. Method: in this study this research in an analytic survey using case control design or caase control is related to how risk factors are studied using retrospective approach.in this study the population is pregnant women TM Nganjuk from January to june 2017. Populationin this study based on data from RSUD Nganjuk is 254 pregnant women TM III the sample of this study is TM III pregnant women in the month January to june 2017 large sample are in use is 154 from the data collection in the analysis with chi square test. Results: After doing calculation hence found count bigger than table (3,84) hence ho rejected, so it can be concluded that there is relation between frequency of Antenatal Care with Genesis Anemia in pregnant mother Trimester III. Conclusion: Based on result of analysis,it can be concluded that there is a significant relationship between the frequency of antenatal Care with the incidence of anemia in pregnant women.